2022
DOI: 10.1590/1519-6984.235573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen and phosphorus availability on the early growth of two congeneric pairs of savanna and forest species

Abstract: In the tropical region, savannas and seasonal forests, both highly diverse biomes, occur side by side, under the same climate. If so, that mosaic cannot be explained solely by climatic variables, but also by fire, water availability and soil status. Nutrient availability in the soil, especially nitrogen and phosphorus, has been postulated to explain the abrupt transitions between savannas and seasonal forests in tropical regions. Plants from these two biomes may present different nutritional strategies to cope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Functional attributes that promote efficient growth are usually the same that increase invasion success (Lamarque et al, 2011). Indeed, in forest environments, taller trees with small but nitrogen‐rich leaves allow a high metabolic efficiency by sustaining high photosynthetic rates and low water loss (Paganeli & Batalha, 2021; Paganeli et al, 2020). These nitrogen‐rich leaves may be connected to the mycorrhizal association (Gorzelak et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Functional attributes that promote efficient growth are usually the same that increase invasion success (Lamarque et al, 2011). Indeed, in forest environments, taller trees with small but nitrogen‐rich leaves allow a high metabolic efficiency by sustaining high photosynthetic rates and low water loss (Paganeli & Batalha, 2021; Paganeli et al, 2020). These nitrogen‐rich leaves may be connected to the mycorrhizal association (Gorzelak et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when considering analogous traits, Weemstra et al (2022) reported that intraspecific variation was greater in root traits compared to leaf traits. Higher ITV in fine-root traits compared to aboveground traits could be due to the heterogeneity in soil conditions and microbial interactions that promote a greater variation within species as individuals uniquely adapt to their immediate soil environment (Paganeli and Batalha, 2021;Weemstra et al, 2022;Spitzer et al, 2023). This also leads to a stronger below-than aboveground competition among conspecifics, arising from differential responses to the heterogeneous belowground conditions over time (Read et al, 2017).…”
Section: Discussionmentioning
confidence: 99%